Georgia Architectural and Historic Properties Survey of Willis St. [3], Sycamore, Turner County, Ga., 1981 - Barton and Harbin (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Willis St. [3], Sycamore, Turner County, Ga., 1981. Georgian plan house with hipped and gabled roof with pediment gable on front. Diamond vents in gables. Shed porch supported by square posts of brick. Clapboard siding. Double sash windows with 6/6 lights. Interior chimney. Transom over front door, which is original and has stained glass. Brick piers. Good condition. Date of Construction: c. 1910. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough.
Georgia Architectural and Historic Properties Survey of Willis St. [3], Sycamore, Turner County, Ga., 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 53.3 MB (55,991,064 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Sycamore (Ga.); Turner County (Ga.)